(untitled) (World Economics and Finance Bulletin, 2026)
This study proposes an integrated methodological model for assessing the efficiency of Remote Electronic Customs Declaration (RECD) posts in Uzbekistan. The model combines process analysis, systems thinking, and functional-cost analysis to identify operational inefficiencies and improve decision-making. Based on national data and international experience from Singapore, South Korea, and Germany, the research highlights key bottlenecks and resource imbalances in customs procedures. The findings show that digital tools are not being fully utilized despite increasing workloads. The model’s flexible structure allows its application not only in customs administration but also in other areas of digital public governance. Overall, the study offers a scalable and data-driven framework for improving institutional performance in the digital era.